DAM STABILITY EVALUATIONUSING SOIL SHEAR STRENGTH PARAMETERS WITH LARGE SCALE IN SITU-DIRECT SHEAR TESTS AND TRIAXIAL TESTS(CASE STUDIES ON THE SEMANTOK DAM PROJECT) - Umam Azzaqy, Akhyaarul
This study that conducted to verify actual Semantok Dam factor of safety that analyzed using the Limit Equilibrium Analysis (LEA) method. The analysis was carried out using the actual embankment shear strength parameters in the field and compared with the design parameters/criteria. The tests include: compaction tests for maximum and minimum density by water replacement method, large-scale triaxial testing, in situ shear strength testing (large-scale direct shear), constant head permeability testing, gradation, and soil properties. To obtain the actual parameters of the Dam embankments, by conducting direct shear tests, its allow in situ calculations, using large shear samples where failure was generated for different normal loads. These experimental values were then used to obtain more reliable values for the equivalent friction angle and roughness of the random soil backfill material. The experimental results obtained from the in situ tests were compared with those predicted by the shear criterion, then the embankment dam safety coefficient was determined using the Geostudio computer program (SlopeW, SigmaW and SeepW). The results of the stability study of the Semantok Dam, which is a random earthfill dam with an upstream slope configuration of 1V : 3.0H and a downstream slope of 1 : 2.75H, show that this dam is safe for the these conditions : end of construction , as well as operation on long term. ( steady seepage and rapid drawdown) by accommodating earthquake loads with a limit of ground shaking at the study site with a probability of 50% (during the building period) is not exceeded in 50 years (OBE) and 5,000 years (MDE). The results of the deformation analysis for dam conditions with MDE earthquake loads using software analysis obtained a deformation value of 14-16 cm. Based on the results of the seepage analysis, it can be concluded that the filtration flow capacity (Qh) of 0.01425 m3/s or 1.231 m3/day fulfills the requirements of Qh < 1% of the annual average runoff and Qh < 0.05% of the gross storage capacity.